Diagnóstico de la producción y comercialización de frutilla (Fragaria Spp.) en la parroquia de Yaruquí, provincia de Pichincha - Bolaños Álvarez, Rina Alexandra (My University, 2010)
Ecuador is entering a firm foothold in the business of production and marketing of strawberries, which has made the study of marketing techniques, information technology and practice, has improved. Among the most strawberry varieties grown in Ecuador, especially in the area Yaruquí, we find the big Bear, Albion, Camino Real, among others. Using traditional technology The changing global competitive environment is a complex reality, making it essential to develop technologies for the agricultural reality in our country. Among the main problems facing the development of growing strawberry (Fragaria spp.) Is the vulnerability to pests and diseases such as Botrytis cinerea, Fusarium spp, Anthracnose, among others. Because of this, it is developing a training program by the strawberry-producing partnerships in the area to be the proper use of chemicals for each pest or disease. Promoting the production and marketing of strawberries would be very important to strengthen the economies of small and medium producers in the area. For which the following objectives: • To determine the production and marketing of strawberries • To determine the prospects for strawberry production to ensure balance over time. • Establish the technology being used in strawberry production. • To know the production process, packaging and transportation. • Identify the product's marketing channels in the area. This investigation was conducted in the province of Pichincha, Quito canton, parish Yaruquí; Otón areas of San Vicente Veliz and 2600 meters over see level. The questionnaire will proceed to try to 10% of the sample; the same questions will consist of clear and easily understood by respondents, with the purpose of correcting errors that exist in the same 100 The variables that were considered are: land tenure, soil type, land preparation, origin of plant material, planting time, weed incidence, incidence of pests and diseases, fertilization and fertilizer use, performance, target production, availability of credit, who performed the various tasks, environmental factors, storage, institutions with which they work, use and management of land, cultivated land, total area, harvesting and packaging, marketing and transportation. It's important to continue the study of insects and diseases in the strawberry crop in the study areas, thus generate more knowledge, both technical, bio- ecological, taxonomic and epidemiological studies of insects and diseases in the strawberry crop
Keywords: FRUTILLA (FRAGARIA SPP.); PARROQUIA DE YARUQUÍ; PROVINCIA DE PICHINCHA